Distribution of potentially pathogenic bacteria in the groundwater of the Jianghan Plain, central China. (September 2019) - Wu, Geng; Yang, Jian; Jiang, Hongchen; Deng, Yamin; Lear, Gavin
Abstract: Pathogenic bacteria are frequently detected in groundwater. However, little is known about the abundance and diversity of potentially pathogenic bacteria and their influencing factors in the groundwater of the Jianghan Plain (JHP), one of the most densely habited areas in central China. Here, we investigated the diversity and abundance of potentially pathogenic bacteria in 156 groundwater samples collected from one 400 km 2 area of the JHP by using 16S rRNA-based Illumina sequencing and quantitative PCR. A total of 193 potentially pathogenic bacterial species were identified in the studied groundwater. Phylogenetic results showed that opportunistic pathogenic Acinetobacter baumannii -like and enteric pathogenic Vibrio cholerae -like bacteria were most prevalent, occurring in 99% and 32% of the studied groundwater samples, respectively. Spatial factors contributed more (5.5% vs 2.4%) than the measured environmental factors to shaping of the potentially pathogenic bacterial distribution, although a large proportion (92.0%) of variation was unexplained. The groundwater temperature was the most important measured factor influencing the abundances of the identified potentially pathogenic bacterial species. In addition, certain opportunistic pathogenic bacterial species showed statistically significant co-occurrence in the studied JHP groundwater samples. Collectively, this data of this study provide new insight into the diversity, distribution and influencing factors of potential pathogens in the JHP groundwater. Highlights: Potentially pathogenic bacteria were abundant and diverse in the Jianghan Plain groundwater. Most of the potentially pathogenic bacteria appeared to be opportunistic pathogens. Spatial and environmental factors affect the potentially pathogenic bacteria distribution. Some of the potentially pathogenic bacteria showed co-occurring pattern.